Detection Of Treatment Adherence, Disease Control and Its Predictors in Asthma Patients by Rural Community Level Health Workers - Prianka Mukhopadhyay; Sumanta Chakraborty; Manisha Sarkar (Medsci Publications, 2022)
Background: Despite the availability of effective therapy, disease control in Asthma remains suboptimal with high morbidity. Objectives: To assess treatment adherence, asthma control and its influencing factors. Methodology: A prospective, observational study was conducted among 152 adult asthma patients reporting consecutively to a BPHC for twelve months. Patients were followed up by trained healthcare workers to assess their treatment adherence and disease control using a predesigned, pretested and validated questionnaire. Results: Mean age was 49.6 years (SD = +14.0), males reported more cases (73.7%), addiction to tobacco was high (48.7%). 40.8% patients had high treatment adherence. Only 37.5% patients reported good asthma control of which 68.4% showed high adherence. The mean Asthma Control Test (ACT) score was 18.75 ± 4.8 SD. Increasing age (aOR=0.96, 95% CI= 0.93-0.99), tobacco smoking (aOR=2.90, 95% CI=1.20-6.99), dust allergy (aOR= 7.92, CI =3.15-19.91) and low treatment adherence (aOR=5.33, 95% CI=2.22-12.82) were found to be significant predictors of poor disease control. Conclusions: Non adherence to treatment and poor disease control were high among rural asthma patients. Patient education for tobacco cessation and treatment compliance along with periodic monitoring undertaken by trained health workers can be an effective strategy to reduce disease burden in the community.